Phase 2, multicenter, open‐label study of tigatuzumab (CS‐1008), a humanized monoclonal antibody targeting death receptor 5, in combination with gemcitabine in chemotherapy‐naive patients with unresectable or metastatic pancreatic cancer. (25th October 2013) - Forero‐Torres, Andres; Infante, Jeffrey R.; Waterhouse, David; Wong, Lucas; Vickers, Selwyn; Arrowsmith, Edward; He, Aiwu Ruth; Hart, Lowell; Trent, David; Wade, James; Jin, Xiaoping; Wang, Qiang; et al.
Abstract Tigatuzumab is the humanized version of the agonistic murine monoclonal antibody TRA‐8 that binds to the death receptor 5 and induces apoptosis of human cancer cell lines via the caspase cascade. The combination of tigatuzumab and gemcitabine inhibits tumor growth in murine pancreatic xenografts. This phase 2 trial evaluated the efficacy of tigatuzumab combined with gemcitabine in 62 chemotherapy‐naive patients with histologically or cytologically confirmed unresectable or metastatic pancreatic cancer. Patients received intravenous tigatuzumab (8 mg/kg loading dose followed by 3 mg/kg weekly) and gemcitabine (1000 mg/m2 once weekly for 3 weeks followed by 1 week of rest) until progressive disease (PD) or unacceptable toxicity occurred. The primary end point was progression‐free survival (PFS) at 16 weeks. Secondary end points included objective response rate (ORR) (complete responses plus partial responses), duration of response, and overall survival (OS). Safety of the combination was also evaluated. Mean duration of treatment was 18.48 weeks for tigatuzumab and 17.73 weeks for gemcitabine. The PFS rate at 16 weeks was 52.5% (95% confidence interval [CI], 39.3–64.1%). The ORR was 13.1%; 28 (45.9%) patients had stable disease and 14 (23%) patients had PD. Median PFS was 3.9 months (95% CI, 2.2–5.4 months). Median OS was 8.2 months (95% CI, 5.1–9.6 months). The most common adverse events related to tigatuzumab were nausea (35.5%), fatigue (32.3%), and peripheral edema (19.4%). Tigatuzumab combined with gemcitabine was well tolerated and may be clinically active for the treatment of chemotherapy‐naive patients with unresectable or metastatic pancreatic cancer.